Students' Perspectives of a Community-Based Medical Education Programme in a Rural District Hospital. (November 2019) - Adefuye, Anthonio; Benedict, Matthew; Bezuidenhout, Johan; Busari, Jamiu O
Background: The adoption of community-based medical education( CoBME) into the undergraduate medical curriculum is in line with the SPICE model for medical curriculum proposed by Harden and colleagues. Students are the consumers of medical education and are, thus, the ideal evaluators of the efficacy of their own course and learning environment. To evaluate the quality of the CoBME programme in Botshabelo District Hospital (BDH), this study investigated student's perceptions of their experience during their CoBME training at BDH. In addition, suggestions on how to enrich students' experience during the CoBME posting were obtained from the participants. Methods: This research was designed as a qualitative (ethnographic) study that used a structured questionnaire, to obtain written statements from 120 fourth-year undergraduate medical students describing their experience during their CoBME training at BDH. The structured questionnaire in the form of an evaluation form was self-administered, consisted of only open-ended questions grouped into 4 main sections and was distributed manually (hard copy) to the participants. Results: Of the 120 questionnaires distributed, 84 were returned, giving a response rate of 70.0%. When asked to indicate what they liked or disliked about their CoBME training, 'Good educators/staff' and the 'Poor attitude of some doctors' were the themes that scored highly (25.1% and 19.4%) in the 'likes' and 'dislikes' category, respectively. Some of the major challenges faced during the CoBME training at BDH included: exposure to new learning environment (14.2%), clinical practice context (12.6%), and language barrier (7.2%). Participants stated that they gained knowledge of how to perform certain clinical procedures and acquired core clinical skills in the areas of formulating management and managing some medical emergencies during their training at BDH. Increasing the duration of training (25.6% coverage) was suggested as a major way to enrich students' experience during the training at BDH. Conclusion: Findings by this study reveal that CoBME is a valuable pedagogical tool to enhance learning in undergraduate medical education and that more work is required to improve the quality of CoBME training in BDH. We believe that the findings by this study will inform future planning of CoBME training programmes in BDH.